ANALISIS PERSONAL BRANDING WILLIAM ADITYA SARANA SEBAGAI POLITISI MUDA MELALUI MEDIA SOSIAL INSTAGRAM - Aldapratiwi, Cyntia; Wahyono, Agus (Jurnal Manajemen, 2024)
The revolution in the digital era, supported by current technological advancements, makes it easier for people to connect and interact with each other. Social media, especially Instagram, has become an effective tool for political figures to build personal branding and conduct digital political campaigns. This study focuses on the formation of William Aditya Sarana's personal branding on Instagram using Rampersad's (2008) authentic personal branding criteria, which includes eight characteristics: authenticity, integrity, consistency, specialization, relevance, visibility, persistence, and good behavior. This research uses a qualitative descriptive approach and a case study research method. Data were obtained through in-depth interviews and document studies. The results of the study show that William Aditya Sarana successfully fulfills the eight characteristics of authentic personal branding, enabling him to build a strong, authentic, and positive personal brand on Instagram. This effective personal branding fosters trust in the minds of the audience, attracting more people and increasing their interest in his political development, thereby gaining votes in elections. These findings indicate the importance of social media in personal branding strategies for political figures in the digital era. Keywords: personal branding, Instagram, social media.